Pharmily enrichment programme 2024 / Dg Siti Nur Anisah Gani and Gurmeet Kaur Surindar Singh - Gani, Dg Siti Nur Anisah; Singh, Gurmeet Kaur Surindar (Faculty of Pharmacy, 2024)
The Pharmily Enrichment Programme 2024, a collaborative initiative by the two student societies from the Faculty of Pharmacy, UiTM Puncak Alam, namely the Sekretariat Mahasiswa Fakulti (SMF) and the Society of Pharmacy Students (SOPHYS), unfolded over April 27th, 28th, and May 15th, with resounding success. The program aimed to provide final semester students (RX19) of the Faculty of Pharmacy with invaluable exposure to diverse career opportunities within the pharmacy field and insights into life after completing their pharmacy education.